Interactions between local and migrant workers at the workplace - Gil S. Epstein; Yosef Mealem (Institute for the Study of Labor (IZA), 2010)
In this paper we consider the interaction between local workers and migrants in the production process of a firm. Both local workers and migrants can invest effort in assimilation activities in order to increase the assimilation of the migrants into the firm and thereby increase their interaction and production activities. We consider the effect of the relative size (in the firm) of each group and the cost of activities on the migrants' assimilation process.
Keywords: D74; F23; I20; J61; L14; 330; Assimilation; contracts; ethnicity; market structure; networks; harassment; Arbeitsplatz; Arbeitskräfte; Ausländische Arbeitskräfte; Soziale Beziehungen; Soziale Integration; Theorie